Draft Annual Plan 2009-10 Government of Goa - Planning Commission (Planning Commission, 2009)
The Government of Goa, within the overall frame of the concept “towards faster and more inclusive growth” in the Approach Paper for the Eleventh Five Year Plan prepared by the Planning Commission has evolved its own strategy, targets and benchmarks for the Eleventh Five Year Plan. Goa has impressive socio-economic indicators. The social indicators of the State like literacy, birth rate, death rate, infant mortality rate etc. are impressive and are the best in the country. Many of these are comparable with the developed nations in the world. Goa has reached the level of replacement in population growth more than a decade ago.
Government of Goa, Directorate of Planning, Statistics and Evaluation